Apoptosis, Pyroptosis, and Ferroptosis Conspiringly Induce Immunosuppressive Hepatocellular Carcinoma Microenvironment and γδ T-Cell Imbalance - Hu, Yi; Chen, Dan; Hong, Minjing; Liu, Jing; Li, Yijia; Hao, Jianlei; Lu, Ligong; Yin, Zhinan; Wu, Yangzhe (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is highly malignant and prone to metastasize due to the heterogeneous and immunosuppressive tumor microenvironment (TME). Programmed cell deaths (PCDs) including apoptosis, ferroptosis, and pyroptosis routinely occur in the HCC TME and participate in tumorigenesis. However, how apoptosis, ferroptosis, and pyroptosis are involved in constructions of the immunosuppressive TME and their underlying cross-talk remains to be further unveiled. In this work, we deciphered the immunosuppressive landscape of HCC TME, which demonstrated high expressions of inhibitory checkpoint molecules and infiltration of protumor immune cells but low infiltration of antitumor effector immune cells. Further investigations unequivocally revealed that marker genes of apoptosis, ferroptosis, and pyroptosis are closely correlated with expressions and infiltrations of inhibitory checkpoint molecules and immune cells and that higher “-optosis” links to poorer patient prognosis. Notably, such three types of “-optosis” interact with each other at both the gene and protein levels, suggesting that they conspiringly induce the establishment of the immunosuppressive HCC TME. Interestingly, examinations of circulating γδ T cells in HCC patients revealed a noticeable dysfunction phenotype. The strikingly elevated ratio of the Vδ1+ versus the Vδ2+ subset suggested that the Vδ1+/Vδ2+ ratio would be a potential biomarker for the diagnosis and prognosis in HCC patients. Altogether, this work thoroughly decrypted the underlying correlations between apoptosis, ferroptosis, and pyroptosis and the formation of immunosuppressive HCC TME and, meanwhile, indicated that allogeneic Vδ2+ γδ T-cell transfer would be a promising adjuvant strategy for renormalizing circulating γδ T cell and thus achieving sound clinical efficacy against HCC.